Economic analysis for effects of policies to support price of products and prices of inputs for meat in Iraq - Man, Norsida; Hussein, Sarmad Ali; Abd. Latif, Ismail; Kamarulzaman, Nitty Hirawaty (Canadian Center of Science and Education, 2017)
This work aims to measure the cost of supporting both the product price support policy and also support input prices, then the comparison between the two policies for their preference between them. The problem of study that the state when implementing the two policies bear sums from the public treasury. Analysis based on the collection of data from the sample of study, a beef and fish meat contains time series on prices, production and consumption depends on the style of mathematics to get the results. The results arrived that the state gets revenue through support product price policy, but the returns were not in the producers have been negatively affected consumer prices up meat. On the other hand the state bore the costs by supporting input prices in order to be provided to producers. Therefore we prefer the input support policy for the economic and productivity. The study recommends that support the agricultural sector policy planning and rehabilitation support commodity price policy.